Pengaruh Tingkat Bunga dan Resiko Kredit terhadap Pendapatan pada PT. Bank Danamon Indonesia Tbk - Hairudin, Hairudin; Hasbullah, Hasbullah; Rachmadi, Agung (Universitas Mitra Indonesia, 2020)
AbstractThe influence interest rate and credit risk to income at PT Bank Danamon Indonesia Tbk. The purpose of this research is to know influence that happened between interest rate and credit risk to income that be measured with use variable interest rate and credit risk to income to company PT Bank Danamon Indonesia Tbk. Sample that used is report finance PT Bank Danamon Indonesia Tbk 2009-2016 years. Technique data analysis research use analysis regression linear multiple. Based on the test simultaneous results of the research showed variable independent interest rate and credit risk on the together influential positive significant cantly to income at PT Bank Danamon Indonesia Tbk. Results partial test showed interest rate influential negative significant to income at PT Bank Danamon Indonesia Tbk, results partial test showed credit risk influential positive significant to income at pada PT Bank Danamon Indonesia Tbk.Keywords: Interest Rate, Credit Risk, and Income.